Analysis of Factors Affecting Intention in Using Google Classroom in Post-Pandemic Era with UTAUT2 Approach - Enrico Samuel Djimesha; Erma Suryani (Fakultas Ilmu Komputer, Universitas Klabat, 2024)
A pandemic that happened a few years ago has forced universities around the world to adopt online learning. This was driven by government regulations that forced society to adopt health protocols and social distancing. The adoption of Google Classroom as a learning management system (LMS) has potential for universities because of its relatively lower cost than other LMSs, its ability to integrate with Google Meet, an online video conference application, and its ability to help manage learning files. XYZ University provides learning management services through Google Classroom. However, the usage of this LMS post-pandemic decreases after the social distancing regulation is lifted. This has become attention for the researcher to analyze and give recommendations to XYZ University on improving the usage of Google Classroom in the post-pandemic era to digitalize and centralize the learning process in a system. The researcher has designed the research stages, starting with problem formulation, using the UTAUT2 approach, analysis with PLS-SEM, and providing recommendations for the university. This model resulted in two factors affecting the acceptance of Google Classroom: performance expectancy and habit. Also, this model explains 56.5% of behavioral intention on using Google Classroom and 59.9% of use behavior of Google Classroom. This study recommends the institution to enforce the use of Google Classroom for every learning activity so that both faculty members and students are used to using it. This study also recommends the institution to socialize about the features and advantages of Google Classroom to help users aware of the positive impact of using Google Classroom on learning activities.